Factors affecting community pharmacists' intention to provide smoking cessation services in Manila City using the theory of planned behavior - Escote, Jemimah Gyra C.​; Ordoñez, Trissia Marie B.​; Sombillo, Maria Celine Isabel V.​; Loquias, Monet M.​ (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2018.)
Implementation of smoking cessation services is important due to the significant effects of cigarette use to morbidity and mortality rates. Provision of the said services by community pharmacists are proven to be effective. However, there is a lack of these services in the Philippines despite the presence of international and local support and guidelines. Hence, this study aimed to determine the factors that might affect the intention of community pharmacists to provide smoking cessation services in Manila City using the Theory pf Planned Behavior (TPB). This study used cross-sectional correlation design which utilized self-administered questionnaire. Descriptive statistics and multiple linear regression were used in data analysis.
Of the 132 pharmacists randomly selected, 72 (54.55%) participated in the study. Results revealed that community pharmacists have average knowledge, positive attitude, favorable subjective norms, more perceived behavioral control, and strong intent toward the provision of smoking cessation services. The TPB model explained 49.3% of the variation in intention and perceived behavioral control was the only significant predictor of intent (p<0.05). Identified barriers were difficulty of providing smoking cessation services, lack of resources, pharmacists' perception on patients' attitude towards their provision of said services, and insufficient knowledge on certain topics. The conduct of seminars and trainings on smoking cessation with corresponding Continuing Professional Development (CPD) units by relevant institutions and the inclusion of smoking cessation interventions in the curriculum by schools of pharmacy are recommended.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, May 2018.
Keywords: Smoking cessation